Aspek Hukum Pembiayaan Infrastruktur Jalan - Denico Doly (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2010)
Road infrastructure is one that must be constructed in Indonesia. Road construction requires huge capital. Government in order to built roads, make a joint venture with infrastructure-financing institution. Financing institutions is one important institution in Indonesia. Financial institution regulated in Presidential Regulation No. 9 of 2009 on Financing Institutions. Juridical arragements regarding financing institutions have been inadequate. This is because the arragement of financing institutions are regulated in the presidential and ministerial decrees. The importance of these financial institutions need a clear arragement and can also be a “legal foundation” in the regulation of financial institutions. This paper will analyze the legal aspects of infrastructure financing in Indonesia.